PENGARUH LOCUS OF CONTROL DAN MOTIVASI TERHADAP KINERJA DENGAN MEDIASI KEPUASAN KERJA (Studi Pegawai Di Puskesmas Se-Eks Kawedanan Tayu) (Jurnal Mahasiswa Pasca Sarjana, 2014)
Teachers as educators is an educational leader, which is crucial in the learning process. Less than optimal performance of early childhood educators in District Pati, is a problem that must be addressed. Early childhood educator competencies and job characteristics in teaching should be improved as well as a strong commitment to be created and to use order to obtain higher performance. This study aims to determine the effect of teacher competence and job characteristics on performance by mediating organizational commitment                (studies in early childhood education teachers in the district Pati). The research was conducted on early childhood education in the District of Starch penddik 140 people. Sample taking the entire population for the research sample . Analysis of the validity of the test data using the components of the matrix , Cronbach alpha reliability test , multiple regression analysis , t test and test with an adjusted r 2 r square. Results reveal that the competence effect on organizational commitment . Positive effect on the employment characteristics of organizational commitment . Competence has a positive effect on the performance of early childhood educators. Job characteristics affect employee performance early childhood educators . Organizational commitment has a positive effect on the performance of early childhood educators. Organizational commitment did not mediate the effect of competence on the performance of early childhood educators. Organizational commitment did not mediate the effect of job characteristics on the performance of early childhood educators. Keywords : Competence, job characteristics, organizational commitment and performance